Functional yogurt: a comprehensive review of its nutritional composition and health benefits - Pannerchelvan, Sangkaran; Rios-Solis, Leonardo; Wasoh, Helmi; Mohd Sobri, Mohamad Zulfazli; Faizal Wong, Fadzlie Wong; Mohamed, Mohd Shamzi; Mohamad, Rosfarizan; Halim, Murni (Royal Society of Chemistry, 2024)
Functional yogurt, renowned for its enhanced nutritional profile and potential health benefits, has emerged as a promising functional food. This review meticulously examines the nutritional composition of functional yogurt, highlighting its enriched content of probiotics, prebiotics, synbiotics, antioxidants, vitamins, minerals, proteins, and other bioactive compounds, which contribute to its health-promoting properties. Functional yogurt has positively affected digestive health, immune function, metabolic health, and mental well-being. It benefits digestive health by alleviating diarrhoeal symptoms, constipation, colon cancer, irritable bowel syndrome (IBS), Helicobacter pylori infection, and digestive-related allergies. Moreover, the immune-boosting properties of functional yogurt play a pivotal role in reducing the risk of infections and inflammation. In addition, functional yogurt has the potential to improve metabolic health, leading to decreased cholesterol levels and enhanced blood sugar regulation. Emerging research also suggests functional yogurt may positively influence mood, behavior, and cognitive function. Functional yogurt is a valuable addition to the human diet, holding significant implications for public health. In addition to its numerous health benefits, functional yogurt also faces limitations, such as the stability of functional compounds, sensory alterations, potential digestive discomfort, and inconsistent efficacy across populations, highlighting the need for further research and optimization.